Point Prevalence of Pediatric Inflammatory Bowel Disease in New Zealand in 2015: Initial Results from the PINZ Study. Issue 8 (24th May 2017) - Lopez, Robert N.; Evans, Helen M.; Appleton, Laura; Bishop, Jonathan; Chin, Simon; Mouat, Stephen; Gearry, Richard B.; Day, Andrew S.
Abstract : Background: The incidence of pediatric inflammatory bowel disease (IBD) around the world is increasing. However, there is a scarcity of data on the epidemiology of pediatric IBD in the Southern Hemisphere. This study aimed to document the point prevalence of pediatric IBD in New Zealand on June 30, 2015. Methods: All patients in New Zealand, under 16 years of age, with a diagnosis of IBD on June 30, 2015 were identified. Demographic and disease phenotypic details were collected and entered into a secure database. Age-specific population data for New Zealand were obtained and national and regional prevalence rates were calculated. Results: The point prevalence of pediatric IBD, Crohn's disease, ulcerative colitis, and inflammatory bowel disease unclassified in New Zealand on June 30, 2015 was (95% confidence intervals) 21.7 (18.9–24.8), 16.5 (14.0–19.2), 3.3 (2.2–4.6), and 1.9 (1.2–3.0) per 100, 000 children, respectively. There was a striking disparity between the prevalence rates in the North and South Islands. Conclusions: The point prevalence of pediatric IBD in New Zealand represents the first-ever national, population-based prevalence rates of pediatric IBD published. Results from the Paediatric IBD in New Zealand (PINZ) study are also the first to show markedly higher prevalence rates of IBD in the southern part of a country compared with its northern counterpart. Ongoing prospective ascertainment of the incidence of pediatric IBD is required.